After Eden : the evolution of human domination - Sale, Kirkpatrick (Duke University Press, 2006)
"In After Eden, Kirkpatrick Sale answers these questions in a radically new way. Integrating research in paleontology, archaeology, and anthropology, he points to the beginning of big-game hunting as the origin of Homo sapiens' estrangement from the natural world. Sale contends that a new, recognizably modern human culture based on the hunting of large animals developed in Africa some 70,000 years ago in response to a fierce plunge in worldwide temperature triggered by an enormous volcanic explosion in Asia. Tracing the migration of populations and the development of hunting thousands of years forward in time, he shows that hunting became increasingly adversarial in relation to the environment as people fought over scarce prey during Europe's glacial period between 35,000 and 10,000 years ago. By the end of that era, humans' idea that they were the superior species on the planet, free to exploit other species toward their own ends, was well established. Sale asserts that vestiges of a more ecologically sound way of life do exist today, offering redemptive possibilities for ourselves and for the planet."--Jacket